Effectiveness of Grass-root Level Unit in Extension Delivery Services in Karnataka - A. Dympep; S. S.Dolli (Indian Journal of Extension Education, 2016)
Timely and relevant access to information and input by farmers is necessary to improve agricultural productivity. A demand driven extension system at the grass-root level called Raitha Samparka Kendras (RSKs) was established in Karnataka in the year 2000 replacing the earlier Training and Visit system (T&V). The study was conducted to analyse the effectiveness of the extension services provided by RSKs in terms of its outreach to the farmers and its impact on their agricultural production. Six RSKs of Gadag district of North Karnataka comprising of six Agricultural Officers (AO), 25 Assistant Agricultural Officers (AAO) and 90 beneficiary farmers were selected. The study revealed that RSKs covered wide geographical area and the ratio of extension personnel to farm families was high (1:1406). It was found that majority (85.56%) of the farmers’ preferred to consult progressive farmers for agricultural information. No significant association was found between farmers’ frequency of contact with their location from RSK as well as with their size of landholding. However, there was a significant association between the farmers’ land holding and extension participation. Asignificant impact was observed on yield of important crops after attaining the services from RSKs. Most of the farmers were primarily using RSK just as government retail outlet to buy subsidized agro-inputs rather than for attaining technical agriculture information.